2006
DOI: 10.1210/me.2006-0068
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-Specific Phosphorylation of the Estrogen Receptor Changes Receptor Interactions with Ligand, Deoxyribonucleic Acid, and Coregulators Associated with Alterations in Estrogen and Tamoxifen Activity

Abstract: Posttranslational modifications of the estrogen receptor (ER) are emerging as important regulatory elements of cross talk between different signaling pathways. ER phosphorylation, in particular, has been implicated in the ligand-independent effects of ER and in tamoxifen resistance of breast tumors. In our studies, Western immunoblot analysis of endogenous ER in parental MCF-7 cells reveals specific, ligand-dependent phosphorylations at S118 and S167, with this ligand dependence being lost in tamoxifen-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(145 citation statements)
references
References 58 publications
8
136
1
Order By: Relevance
“…2B) (Paszek et al, 2005). Interestingly, force-generated activation of ERK may also influence cell proliferation, alter tissue behavior and drive anti-estrogen resistance during breast cancer treatment, through phosphorylation of ERα, recruitment of ERα co-activators or enhanced transcriptional activity, in a ligand-independent manner (Likhite, Stossi, Kim, Katzenellenbogen, & Katzenellenbogen, 2006). Indeed, tamoxifen, the anti-estrogen used in the treatment of breast cancer, has been shown to reduce breast density and therefore the risk of recurrences (Atkinson, Warren, Bingham, & Day, 1999).…”
Section: Associated Pathologiesmentioning
confidence: 99%
“…2B) (Paszek et al, 2005). Interestingly, force-generated activation of ERK may also influence cell proliferation, alter tissue behavior and drive anti-estrogen resistance during breast cancer treatment, through phosphorylation of ERα, recruitment of ERα co-activators or enhanced transcriptional activity, in a ligand-independent manner (Likhite, Stossi, Kim, Katzenellenbogen, & Katzenellenbogen, 2006). Indeed, tamoxifen, the anti-estrogen used in the treatment of breast cancer, has been shown to reduce breast density and therefore the risk of recurrences (Atkinson, Warren, Bingham, & Day, 1999).…”
Section: Associated Pathologiesmentioning
confidence: 99%
“…In breast cancer cells phosphorylation of the Ser-118 residue in the human ERa A/B domain by growth factors stimulated mitogen-activated protein kinase (Kato et al, 1995;Bunone et al, 1996;Chen et al, 2000;Medunjanin et al, 2005;Park et al, 2005;Weitsman et al, 2006) results in the potentiation of the ER ligandindependent transcriptional activation function (AF-1). Interestingly, it has been proposed that phosphorylation in Ser-118 may be associated with an increase in estrogen agonism, progression of breast cancer, resistance to tamoxifen therapy and estrogen-independent growth of MCF-7 cells (Likhite et al, 2006;Murphy et al, 2006). Recently, it has been shown that the pure ER antagonist ICI 182,780 (ICI) can also induce ER phosphorylation in Ser-118 (Lipfert et al, 2006;De los Santos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of ERa-Ser118 by ERK increases binding of coactivator SRC-3 (Likhite et al 2006) and renders ERa hypersensitive to E 2 (Vendrell et al 2005). Phosphorylation of ERa-Ser118 decreases ERa affinity for TAM and reduces binding to DNA, when ERa is TAM-bound (Likhite et al 2006). In a TAM-resistant cell line obtained by selection after prolonged exposure to TAM, ERK activity was found to be elevated and pERa-Ser118 was increased (Vendrell et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Ser-118 is perhaps the best-studied site of ERa phosphorylation and is widely considered to be a target of ERK, although other kinases such as the glycogen synthase kinse-3 (GSK-3), inhibitor of kappa B kinase (IKK) a, cyclin-dependent kinase 7 (CDK7) and mammalian target of rapamycin (mTOR)/ ribosomal protein S6 kinase (p70S6K) may also phosphorylate this site (de Leeuw et al 2011). Phosphorylation of ERa-Ser118 by ERK increases binding of coactivator SRC-3 (Likhite et al 2006) and renders ERa hypersensitive to E 2 (Vendrell et al 2005). Phosphorylation of ERa-Ser118 decreases ERa affinity for TAM and reduces binding to DNA, when ERa is TAM-bound (Likhite et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation